2021
DOI: 10.24953/turkjped.2021.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of functional gastrointestinal disorders with postpartum conditions related to mother and baby

Abstract: Functional gastrointestinal disorders (FGID) in infants are chronic or recurrent symptoms that are age-dependent, and cannot be explained by structural or biochemical problems. Regurgitation, rumination syndrome, cyclic vomiting syndrome, infantile colic, functional diarrhea, infant dyschesia and functional constipation are defined under this group of disorders. These symptoms may be a component of normal development or an inappropriate response to different stimuli. 1 Biopsychosocial model is commonly accepte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Previous research showed that the composition of the intestinal microbiota in infants delivered vaginally is similar to that in the mother's vagina, but the colonization and dominance of Bifidobacteria and Lactobacillus in the intestine of infants delivered by C-section occurs later [2]. This is closely related to metabolism, immunity, intestinal diseases, allergies, neuropsychiatric growth disorders, obesity, diabetes, and other chronic diseases in adulthood [3][4][5][6][7]. Thus, dysbacteriosis of the early intestinal flora that accompanies this procedure has gradually been recognized as an important public health problem [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that the composition of the intestinal microbiota in infants delivered vaginally is similar to that in the mother's vagina, but the colonization and dominance of Bifidobacteria and Lactobacillus in the intestine of infants delivered by C-section occurs later [2]. This is closely related to metabolism, immunity, intestinal diseases, allergies, neuropsychiatric growth disorders, obesity, diabetes, and other chronic diseases in adulthood [3][4][5][6][7]. Thus, dysbacteriosis of the early intestinal flora that accompanies this procedure has gradually been recognized as an important public health problem [8].…”
Section: Introductionmentioning
confidence: 99%
“…Caesarean section (C-section) is one of the most common obstetrical procedures and is increasing in prevalence worldwide (Boerma et al, 2018). Compared with those born vaginally, offspring born via C-section harbour dysbacteriosis of the early intestinal flora (Callaway, 2019;Hoang et al, 2021), which potentially leads to an increased risk of gastrointestinal (GI), immunological, metabolic and neuropsychiatric disorders (Bekem et al, 2021;Miller et al, 2020;Moya-Pérez et al, 2017;Pan et al, 2021). Given the dynamic nature of microbiota development with age (Korpela and de Vos, 2018), the first 1,000 days of lifewhich includes gestation and the first two years of life -are seen as a window of opportunity to compensate for early microbial imbalance and to improve future health in childhood and even adulthood (Francavilla et al, 2018;Hashemi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for the prevalence difference may be due to different diagnostic criteria used, different study respondents, and different geographical location in different studies ( 1 , 5 ). FGIDs do not only have negative impacts on the physical growth and quality of life of affected infants, but also on the emotional status and daily life of the family ( 6 , 7 ). Parents may have less ability to concentrate at work and feel anxious, and even seek to consult a physician frequently, which will not only increase medical costs, but also lead to needless suffering of the caregivers ( 8 , 9 ).Therefore, investigating the prevalence and risk factors of FGIDs in infants are of great clinical importance.…”
Section: Introductionmentioning
confidence: 99%